Strategi Optimalisasi Konfigurasi Ruang Outdoor Kampus dengan Pendekatan Space Syntax - Alifiano Rezka Adi; Sri Pujiati; Ernawati Ernawati; Sulthan Abdurrahman (Universitas Sebelas Maret Surakarta, 2025)
The development of spatial planning in a campus environment requires careful planning to enhance social interaction, comfort, and the efficiency of human movement. This study aims to identify the characteristics of outdoor space configurations on a campus, depicted through circulation networks and gathering spaces as public areas. This study uses a quantitative method with modeling and simulation strategy. The simulation is conducted using space syntax approach through DepthmapX software to analyze outdoor spaces on the Faculty of Ushuluddin and Humanities at UIN Walisongo. The results show that isolated spaces can be better connected to the core areas of the campus by engineering wider access routes and reducing outdoor spatial elements that obstruct accessibility. The increase in spatial connectivity is indicated by the overall integration and intelligence values. This enhancement is expected to create a more inclusive, functional, and efficient campus outdoor space that supports both academic and non-academic activities